2015
DOI: 10.4014/jmb.1409.09094
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Gene Cloning, and Characterizations of an Acid-Stable ��-Amylase

Abstract: Based on its α-amylase activity at pH 5.0 and optimal pH of the crude enzyme, a strain (named B-5) with acid α-amylase production was screened. The B-5 strain was identified as Bacillus amyloliquefaciens through morphological, physiological, and biochemical characteristics analysis, as well as 16S rDNA phylogenetic analysis. Its α-amylase gene of GenBank Accession No. GU318401 was cloned and expressed in Escherichia coli. The purified recombinant α-amylase AMY-Ba showed the optimal pH of 5.0, and was stable at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…4a). In general, native and recombinant a-amylases from Bacillus show optimum activity at neutral or slightly acidic pH, as has been reported for AmyJ33 (optimum pH 5.0) (Herna ´ndez-Heredia and del Moral 2016) AmyQ A and B (optimum pH 7 and 7.5, respectively) (Liu et al 2015); AmyQ (optimum pH 5-7) (Sun et al 2010), AMY-Ba (optimum pH 5) (Liu et al 2015). It is also known that the activity in the most of native a-amylase decreases rapidly at alkaline pH values (Bessler et al 2003;Goyal et al 2005), which seems to apply for some recombinant enzymes (Yang et al 2012) but not for AmyJ33r.…”
Section: Amyj33r Amyj33 Amyj33rsupporting
confidence: 66%
See 3 more Smart Citations
“…4a). In general, native and recombinant a-amylases from Bacillus show optimum activity at neutral or slightly acidic pH, as has been reported for AmyJ33 (optimum pH 5.0) (Herna ´ndez-Heredia and del Moral 2016) AmyQ A and B (optimum pH 7 and 7.5, respectively) (Liu et al 2015); AmyQ (optimum pH 5-7) (Sun et al 2010), AMY-Ba (optimum pH 5) (Liu et al 2015). It is also known that the activity in the most of native a-amylase decreases rapidly at alkaline pH values (Bessler et al 2003;Goyal et al 2005), which seems to apply for some recombinant enzymes (Yang et al 2012) but not for AmyJ33r.…”
Section: Amyj33r Amyj33 Amyj33rsupporting
confidence: 66%
“…TS 23 a-amylase lost the N-terminal when it was expressed in E. coli (Lin et al 1997); in further research, the authors found that the N-terminal is essential for translocation of the enzyme to the culture medium in E. coli (Lo et al 2001). In contrast, the B. amyloliquefaciens a-amylase, AMY-Ba, with 95% of identity with AmyJ33r, was cloned without the signal peptide and expressed in E. coli BL21; the protein of 66 kDa produced was located in the intracellular extract (Liu et al 2015). In the same way, the recombinant a-amylase from B. aquimaris (BaqA, without signal peptide) expressed in the same system was located in the intracellular extract (Puspasari et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar properties of temperature and pH were found in the previous study of Amy1 from B. amyloliquefacien JH‐06 . However, after pre‐incubation at 60 °C, AmyZ3 showed better thermostability compared to AMY‐Ba from B. amyloliquefacien B‐5 . α ‐Amylases find a broad range of applications because of their versatilely pH and temperature characteristics .…”
Section: Resultssupporting
confidence: 83%